Differenza sessuale e ontologia - Zupanĉiĉ, Alenka (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
The paper aims to underline and develop a possible – and intimate – relationship between psychoanalysis and philosophy (specifically ontology) on the basis of the Freudo-Lacanian uncanny and disruptive notions of sexuality and Real. The author outlines the fundamental differences between the psychoanalytic account of sexuality and sexual difference and those produced by contemporary gender studies. Sexuality is considered as a serious issue for ontology, for it is not simply something outside being or outside symbolic - something opposed to being -, but because it works as the curving of the symbolic space caused by the signifying gesture, an “alterity” inside being, so that a topological and structural antagonism can be retrieved at the basis of subject and being. Traduzione di Lorenzo Curti